Job Anxiety, Work‐Related Psychological Illness and Workplace Performance. (12th November 2015) - Jones, Melanie K.; Latreille, Paul L.; Sloane, Peter J.
Abstract: This article uses matched employee–employer data from the British Workplace Employment Relations Survey to examine the relationship between employee psychological health and workplace performance in 2004 and 2011. Using two measures of work‐related psychological health — namely employee‐reported job anxiety and manager‐reported workforce stress, depression and anxiety — we find a positive relationship between psychological ill‐health and absence, but not quits. The association between psychological ill‐health and labour productivity is less clear, with estimates sensitive to sector, time period and the measure of psychological health. The 2004–2011 panel is further used to explore the extent to which change in psychological health is related to change in performance.